Efektivitas Mediasi dalam Penyelesaian Perkara Perdata di Pengadilan Negeri Purwokerto - Fallonne, Anitia Emalia (UM Purwokerto Press, 2024)
Mediation is a form of non-litigation dispute resolution process, mediation must be carried out by parties in civil cases in court, in accordance with article 1 number 7 PERMA No. 01 of 2016. Mediation is considered to be a fast, effective and low-cost civil case resolution process. There are factors that influence the progress of the mediation process in court. These factors can determine the effectiveness of mediation. Therefore, researchers are interested in researching and analyzing the effectiveness of mediation in resolving civil cases at the Purwokerto District Court. The method used in this research is a normative juridical research method, using a qualitative approach, the type of data is secondary data, and uses descriptive data analysis techniques. The results of this research, seen from the percentage of success and failure rates of mediation at the Purwokerto District Court in 2022 and 2023, the percentage of success is smaller than the percentage of failure, but there is an increase in the percentage of mediation success from 2022-2023 which shows progress. And the effectiveness of mediation is influenced by legal factors, law enforcement factors, facility and means factors.